The influence of wearing ski-boots with different rigidity characteristics on postural control - Noé, F.; Garcia-Massó, X.; Delaygue, P.; Melon, A.; Paillard, T. (Sports Biomechanics, 2020)
External supports that reduce ankle joint mobility such as ski-boots can impair postural control of healthy participants. Although this disruptive effect has been attributed to the rigidity of the external supports, the results remained controversial and no study has been conducted in order to evaluate the influence of ski-boots rigidity. Hence, the question about the influence of ankle support rigidity on postural control remains open. This study was therefore undertaken in order to investigate the effect of ski-boots rigidity on postural control. Ten healthy active participants were recruited. The wearing of soft and rigid ski-boots was compared to barefoot while standing on a seesaw generating mediolateral and anteroposterior instability. Centre of pressure displacements were sampled with a force platform. The surface electromyographic activity of the main muscles from the leg, thigh and trunk was recorded. A motion analysis system was also used to calculate the ankle, knee and hip angles. The results did not reveal any negative influence of ski-boot rigidity on postural control but rather suggest a less active postural control with the rigid ski-boots which offered a higher mechanical contribution.